Test time affects Farnsworth D15 outcomes in practiced, but not unpracticed, subjects with color vision deficiency - Cho, Anne Arah; Ng, Jason S. (Optometry and vision science, 2024)
SIGNIFICANCE Imposing a time limit on the Farnsworth D15 test may prevent patients from compromising the test. PURPOSE This study aimed to investigate the effect of test time on the Farnsworth D15 color vision test in unpracticed and practiced subjects and determine an optimal test time. METHODS Twenty-one subjects (mean/standard deviation age, 33.1/9.3 years) with a range of congenital color vision deficiency participated in the study. Pseudoisochromatic plate screening, Farnsworth D15, and anomaloscope testing were performed for classification purposes. At each of 2 visits, 10 trials of the Farnsworth D15 were performed with a range in test times from 30 seconds to 10 minutes. Between visits, subjects practiced the test. Major crossovers were used as the outcome measure. A repeated-measures analysis of variance compared the scores across trials. Post hoc Dunnett's testing analyzed the pairwise data. RESULTS Although no significant difference in the mean number of major crossovers was found across the 10 trials for the first visit (F(9, 180) = 1.30, p=0.24), a significant difference was found for the second visit (F(9, 180) = 4.77, p<0.001). The range of mean number of major crossovers for the second visit was 1.71 to 5.1, with the 30-second trial resulting in the largest number of major crossovers and the longest trial resulting in the smallest number of major crossovers. Analysis showed that a 2-minute time limit resulted in a Farnsworth D15 outcome that would be expected based on the anomaloscope for a majority of subjects. CONCLUSIONS In this study, test time was found to affect performance in practiced subjects but not in unpracticed subjects. Based on this study, we recommend enforcing a time limit of 2 minutes to discourage those who try to pass the Farnsworth D15 through practice. Additional measures, such as recording patient behavior, can also be taken.